Laser-Induced Periodic Surface Nano- and Microstructures for Tribological Applications - Bonse, Jörn; Spaltmann, Dirk (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is the printed edition of the Special Issue published in Materials. The book provides an overview of current international research activities in the field of friction and wear management through the laser processing of periodic surface micro- and nanostructures for technical and medical applications. Contributions of renowned scientists from academia and industry provide a bridge between the fields of tribology and laser material processing in order to foster current knowledge and present new ideas for future applications and new technologies.